Efficacy of intrauterine insemination in women with endometrioma-associated subfertility: analysis using propensity score matching - He Cai; Jinlin Xie; Juanzi Shi; Hui Wang (BMC, 2022)
Abstract Background Intrauterine insemination (IUI) treatment is recommended in subfertile women with AFS/ASRM stage I/II endometriosis. However, the efficacy of IUI in women with ovarian endometriomas with tubal patency is uncertain. We explored the efficacy of IUI for the treatment of endometrioma-associated subfertility. Methods We performed a retrospective matched cohort study using propensity matching (PSM) analysis. Subfertile couples undergoing IUI with and without ovarian stimulation between January 1, 2015, and May 30, 2020 were reviewed. Results After PSM, 56 women with endometrioma alone were matched to 173 patients with unexplained subfertility. The per-cycle pregnancy rate (PR) was comparable between women with endometrioma-associated subfertility (n = 56, 87 cycles) and women with unexplained subfertility (n = 173, 280 cycles) (9.2% vs. 17.9%, OR 0.47; 95% CI, 0.21-1.03). Subgroup analyses based on IUI with or without stimulation also resulted in comparable results. A trend toward a lower cumulative pregnancy rates (CPRs) was seen in women with endometrioma (14.3%, 8/56) compared with women with unexplained subfertility (28.9%, 50/173), but the differences were not significant (HR 0.49; 95% CI, 0.23-1.15). However, patients with endometrioma were nearly twice as likely to converse to IVF treatment compared with those without the disease (60.7% versus 43.9%; OR 1.97; 95% CI, 1.07-3.65). Conclusion IUI may be a viable approach for subfertile women with endometrioma and no other identifiable infertility factor. More studies are needed to reassure the findings.